GetReal in network meta‐analysis: a review of the methodology. (11th January 2016) - Efthimiou, Orestis; Debray, Thomas P. A.; van Valkenhoef, Gert; Trelle, Sven; Panayidou, Klea; Moons, Karel G. M.; Reitsma, Johannes B.; Shang, Aijing; Salanti, Georgia; ,
Abstract : Pairwise meta‐analysis is an established statistical tool for synthesizing evidence from multiple trials, but it is informative only about the relative efficacy of two specific interventions. The usefulness of pairwise meta‐analysis is thus limited in real‐life medical practice, where many competing interventions may be available for a certain condition and studies informing some of the pairwise comparisons may be lacking. This commonly encountered scenario has led to the development of network meta‐analysis (NMA). In the last decade, several applications, methodological developments, and empirical studies in NMA have been published, and the area is thriving as its relevance to public health is increasingly recognized. This article presents a review of the relevant literature on NMA methodology aiming to pinpoint the developments that have appeared in the field. Copyright © 2016 John Wiley & Sons, Ltd.